Experimental determination of convective heat transfer coefficient of some agricultural products in forced convection drying - Akpinar, EK (Pergamon-Elsevier Science Ltd, 2004)
In this paper, a simulation study has been made for determination of the convective heat transfer coefficients of eight agricultural products, namely, mulberry, strawberry, apple, garlic, potato, pumpkin, eggplant and onion under forced convection drying. Data obtained from experimentation under open simulated condition have been used to determine values of the coefficients C and n and, consequently, convective heat transfer coefficient. The values of convective heat transfer coefficient determined 2.007 W/m(2) C for mulberry, 3.615 W/m(2) degreesC for strawberry, 2.874 W/m(2) degreesC for apple, 0.644 W/m(2),degreesC for garlic, 4897 W/m(2) degreesC for potato, 3.530 W/m(2) degreesC for pumpkin, 4.026 W/m(2) degreesC, for eggplant and 7.121 W/m(2) C for onion. The experimental error in terms of percent uncertainty was also calculated. (C) 2004 Elsevier Science Ltd.
Keywords: Mass-Transfer